2019
DOI: 10.1016/j.jss.2018.11.047
|View full text |Cite
|
Sign up to set email alerts
|

GABA, γ-Aminobutyric Acid, Protects Against Severe Liver Injury

Abstract: Background: Acute liver failure (ALF) from severe acute liver injury is a critical condition associated with high mortality. The purpose of this study was to investigate the impact of preemptive administration of γ-aminobutyric acid (GABA) on hepatic injury and survival outcomes in mice with experimentally induced ALF. Materials and Methods: To induce ALF, C57BL/6NHsd mice were administered GABA, saline, or nothing for 7 days, followed by intraperitoneal administration of 500 μg of tumor necrosis factor α an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 67 publications
1
21
0
Order By: Relevance
“…Interestingly, the administration of a high-dose of GABA-enriched germinated adzuki bean to the mice in group TF3 remarkably reduced the TC and TG levels ( p < 0.05, Figures 3A,B ), while the serum levels of ALT, AST, TP, and TB also showed gradually declining trends ( Figures 3C–F ), indicating that the diet administered to the TF3 group had a great protective effect on the liver of the diabetic mice, which may be attributed to a large increase in GABA content in the germinated adzuki beans. Previous studies have confirmed that GABA has anti-diabetic effects, which are mainly achieved by inhibiting obesity-related inflammation and upregulating Treg responses in vivo ( 32 ), and it was recently shown that GABA intervention can effectively protect mice from acute liver injury via GABA-mediated STAT3 signaling ( 33 ). Additionally, in all HFD + STZ-treated T2DM mice, the blood urea and serum creatinine levels decreased in a dose-dependent manner with different dosages of GABA-enriched germinated adzuki bean treatment for 6 weeks ( Figures 3G,H ), which might be associated with reduced serum lipid profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the administration of a high-dose of GABA-enriched germinated adzuki bean to the mice in group TF3 remarkably reduced the TC and TG levels ( p < 0.05, Figures 3A,B ), while the serum levels of ALT, AST, TP, and TB also showed gradually declining trends ( Figures 3C–F ), indicating that the diet administered to the TF3 group had a great protective effect on the liver of the diabetic mice, which may be attributed to a large increase in GABA content in the germinated adzuki beans. Previous studies have confirmed that GABA has anti-diabetic effects, which are mainly achieved by inhibiting obesity-related inflammation and upregulating Treg responses in vivo ( 32 ), and it was recently shown that GABA intervention can effectively protect mice from acute liver injury via GABA-mediated STAT3 signaling ( 33 ). Additionally, in all HFD + STZ-treated T2DM mice, the blood urea and serum creatinine levels decreased in a dose-dependent manner with different dosages of GABA-enriched germinated adzuki bean treatment for 6 weeks ( Figures 3G,H ), which might be associated with reduced serum lipid profiles.…”
Section: Discussionmentioning
confidence: 99%
“…4-aminobutyrate aminotransferase (ABAT), a key enzyme for GABA catabolism and mitochondrial nucleoside metabolism (9), tended to be gene-dosage-dependently decreased in the heterozygote and knockout mice (↓94%). Interestingly, GABA potently protects against severe liver injury (46). Thus, the dramatic down-regulation of ABAT in the knockout mice may impair mitochondrial nucleoside metabolism but protect the knockout mice from liver injury via elevated GABA.…”
Section: Resultsmentioning
confidence: 99%
“…This hypothesis is supported by increased GABA in Ifnar1 -/- livers and by the slightly increased OXPHOS dependency of Ifnar1 -/- macrophages on glutaminolysis compared to wt. Of note, recent reports attribute a protective effect to GABA in both acute liver injury [ 36 ] and L . monocytogenes infection [ 37 ], although involvement of IFN-I signaling has not been addressed in the latter study.…”
Section: Discussionmentioning
confidence: 99%